(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
Students’ interest in reading in Indonesia is still relatively low, influenced by various factors such as the use of smartphones for visual entertainment and the lack of literacy guidance. One way to overcome this problem is through a structured reading literacy program. The 2 Sheets of Reading Every Day Literacy Movement at SDN Pejagan 7, Bangkalan, was designed to increase students’ reading interest and critical literacy skills. This study used a qualitative approach with data collection through observation, interviews and documentation. The program involves the active role of the principal, teachers, students and parents. The data analysis process began before the implementation of activities in the field and continued during the field activities. The steps include the process of summarizing data, displaying data, and making conclusions. The results showed a significant increase in students’ interest in reading, although there were obstacles such as time constraints and book availability. The 2 Sheets of Reading Every Day Literacy Movement proved effective in building a reading culture in elementary schools. However, this program needs strengthening in the aspects of time management, additional book collections, and technology integration to support its sustainability and development in the future.Abstracts should be clear, concise, and descriptive